2020
DOI: 10.4103/jfmpc.jfmpc_57_20
|View full text |Cite|
|
Sign up to set email alerts
|

Association between mid-upper arm circumference and body mass index in pregnant women to assess their nutritional status

Abstract: Background: Underweight/ Undernourished is a state when the body mass index (BMI) falls below 18.5 kg/m2 and as per National Family and Health Survey-4, 22.9% of women in the reproductive age group fall into this category. Despite being considered as an important anthropometry marker, it is not measured in most of the healthcare facilities across India due to lack of basic amenities and resources. In such instances, how helpful other indicators like mid-upper arm circumference (MUAC) can be to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…In an Asian study conducted by Tang et al 9 found a significant positive correlation between MUAC and birth weight of the baby with correlation coefficient of 0.34, which are in accordance to this present study. However, study conducted by Mishra et al 10 found the significant linear relation between MUAC and birth weight with correlation coefficient of 0.57 which is higher than our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In an Asian study conducted by Tang et al 9 found a significant positive correlation between MUAC and birth weight of the baby with correlation coefficient of 0.34, which are in accordance to this present study. However, study conducted by Mishra et al 10 found the significant linear relation between MUAC and birth weight with correlation coefficient of 0.57 which is higher than our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…BMI has conventionally served as a gauge for maternal nutritional status and fetal growth prediction [29]. However, growing evidence is suggesting that MUAC could be used as an alternative in assessing pregnancy outcomes [15,30]. A study in India found a significant association (aOR = 7.91, p-value < 0.001) and also a moderate positive correlation between MUAC and BMI (r = 0.57, p < 0.001), suggesting MUAC to be a simple yet effective tool for assessing maternal nutritional status in pregnancy especially in low resource settings [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, growing evidence is suggesting that MUAC could be used as an alternative in assessing pregnancy outcomes [15,30]. A study in India found a significant association (aOR = 7.91, p-value < 0.001) and also a moderate positive correlation between MUAC and BMI (r = 0.57, p < 0.001), suggesting MUAC to be a simple yet effective tool for assessing maternal nutritional status in pregnancy especially in low resource settings [30]. Results from a Zambian study assessing BMI and MUAC for predicting SGA revealed an inadequate overall predictive model (AUC BMI = 0.66, AUC MUAC = 0.68).…”
Section: Discussionmentioning
confidence: 99%
“…The weighing machine was checked and validated, using known weights, every day before the start of the survey. WC, HC and MUAC were measured using the measuring tape following standard methods 4 .…”
Section: Methodsmentioning
confidence: 99%